Воздействие стороннего электромагнитного излучения на механизмы взаимодействия поверхностных колебаний с электронами проводимости полупроводниковых структур - Кравченко, Владимир Иванович; Серков, Александр Анатольевич; Бреславец, Виталий Сергеевич; Яковенко, Игорь Владимирович (НТУ "ХПИ", 2015)
Разработана теория бесстолкновительного затухания поверхностных поляритонов в квантовом и классическом приближениях. Определены механизмы возникновения неустойчивостей собственных колебаний полупроводниковых сверхрешеток, обусловленных их взаимодействием с потоками заряженных частиц в условиях влияния внешнего электромагнитного излучения. Показано, что влияние импульсного электромагнитного излучения сопровождается возникновением токов в проводящих элементах изделий и возникновением их внутренних полей. Разработан новый механизм появления поверхностных электронных состояний на неровной поверхности проводящих твердых тел. Исследовано влияние неоднородных свойств поверхностей проводящих твердых тел в излучающих структурах на спектральные характеристики переходного и черенковского излучения.

New mechanism of excitation of surface magnito plas mf oscillations by the moving radiation source are suggested. The development of theory of interaction of microwave electromagnetic oscillations and charged particles in bounded plasma-like media and the study of kinetic and hydrodynamic beam instabilities in solid –like structures appled in the present microwave electronics is proposed. The power losses of the flow of charged particles caused by such an interaction due to excitation of surface polaritons in the semiconductor superstructure have been determined. The influence of pulsed electromagnetic radiation on electric radio apparatus is often accompanied by currents arcsing on inner current – conducting elements as well as by the distortion of their internal fields. A new mechanism of initiation of surface at uneven of the conducting solid bodies is proposed. A theory of collisionless damping of surface plasmons in qvantium and classical approcsimations is tlfborated and the conditions of its conversion are determined. The effect of inhomogeneouse properties of surface of open radiating structures on the spectral characteristics of transition radiation is studies. It is found that thte energy losses related to excitation of volume helicons are equivalent to the energy losses of a magnetic moment created due to the charge rotation.
Impact of Side Electromagnetic Radiation on the Mechanism of the Interaction of Surface Oscillations with Conductive Electron sof Semiconductor Structures
Keywords: радиоэлектронная аппаратура; электромагнитные поля; полупроводниковые сверхрешетки; генерирование; геликоны; поверхностные волны; electromagnetic fields; vibrations; semiconductor superlattice; generation; charged particles; surface waves